2001
DOI: 10.1093/jn/131.3.807
|View full text |Cite
|
Sign up to set email alerts
|

Kefir Milk Enhances Intestinal Immunity in Young but Not Old Rats

Abstract: The adjuvant effect of kefir fermented milk on the mucosal and systemic immune systems was examined in young (6 mo old) and old (26 mo old) rats. Kefir-fed rats consisted of young or old rats consuming kefir-fermented milk ad libitum on a daily basis in addition to the standard diet, for 28 d. Control rats consumed only the standard diet. The rats were immunized intraduodenally with cholera toxin (CT) on d 7 and 21 and killed on d 28. The nonspecific serum immunoglobulin (Ig)A titers in kefir-fed and control r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 23 publications
1
38
0
2
Order By: Relevance
“…Previous reports showed that kefir was able to enhance the specific intestinal mucosal immune response against cholera toxin (19). The immunodulating activity of kefir or kefiran (a polysaccharide found in kefir) in tumor bearing mice has been reported (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that kefir was able to enhance the specific intestinal mucosal immune response against cholera toxin (19). The immunodulating activity of kefir or kefiran (a polysaccharide found in kefir) in tumor bearing mice has been reported (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of fermented milk can reduce CRP and TNF-α in rats with high fat diet and decrease the growth rate of mammary tumors through the reduction of proinflammatory cytokines (IL-6) [11,12]. The fermented soybean has an anti-inflammatory activity through the inhibition of proinflammatory cytokines production [13] and kefir is one of the fermented products that is made of milk with a complex mixture of bacteria (lactobacilli, lactococci, leuconostocs, aceterobacteria) and yeast (lactose-fermenting and non lactose-fermenting) [14,15]. Kefir has antioxidant, anticancer, anti-inflammatory, antidiabetic [16,17], and anti-hyperglycemic activities [18,19].…”
Section: Background and Aimsmentioning
confidence: 99%
“…Kefir, a cultured milk beverage, originated in the Caucasus Mountains of Russia centuries ago and has been ascribed with many health benefits including antitumor activity (Shiomi et al, 1982), antimicrobial activity (Cevikbas et al, 1994), enhanced immune function (Thoreux and Schmucker 2001), stress relief (Kabayama et al, 1997), specific health benefit (Otle and Cagindi, 2003) and improved digestion (Safonova et al, 1979). This fermented milk product results from the collective action of multiple microorganisms present in kefir grains in milk (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%